"I see your True Colors": Mitigating grouphate by exploring personality differences. Issue 1 (2nd January 2020) - Hunter, Karla M.; Westwick, Joshua
Abstract : Course: Small Group Communication. Objectives: Students will identify their personality traits; synthesize the relationship between personality, small-group interdependence, and grouphate; and apply collaborative skills and knowledge of individual personality differences in building small-group success.